Business and Society Making Management Education Relevant for the 21st Century (Springer International Publishing, 2018)
The world of business is constantly evolving and management education institutions will likely face a number of challenges in keeping up with these changes. While most books focus on the needs of management education institutions, this work addresses the needs of the corporate world in the era of the Fourth Industrial Revolution. Featuring an extensive research study spanning 11 countries, it offers a unique perspective on the business challenges and developmental needs of companies in emerging and recently emerged economies, and on the missing links between those needs and management education. Using both company-specific and country-level data, the book provides businesses and educators with rare insights and recommendations on strengthening existing partnerships (or establishing them anew) between management education institutions and the corporate sector in order to make management education relevant for the 21st century. The book argues that 'relevance' should take the center-stage of all higher education institutions in order to accomplish their third mission, namely service to society. This is especially important for management education institutions, whose mission is to mold future managers and leaders who can have a significant influence on economic success and the wellbeing of society.